PENYEMPURNAAN TEKNIK PENYADAPAN RESIN PINUS DENGAN METODE KUAKAN - Ika Nugraha Darmastuti; Gunawan Santosa; Juang R. Matangaran (BRIN Publishing, 2016)
Overtapping of pine resin in terms of quare size which is too wide and deep and the use of anorganic stimulant may cause tree damage and increase the risk of tree to fall. Modification of tapping technique may reduce the damage of trees and increase the production of pine resin. The modification should consider several aspects of economical, ecological, social, and technical. The objectives of the research were to determine the width and number of quare on each tree, the appropriate type of organic stimulant, and also cost analysis of the modified tapping technique. The results showed that different type of tapping such as width and number of quare per tree significantly gave different resin production. However, different types of organic stimulant and its interaction with number and width of quare was not correlated significantly with resin production. Modification of tapping techniques and the use of organic stimulant had direct influences on the cost and profit.